2016
DOI: 10.1186/s12906-016-1251-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of synergistic mechanism and identification of interaction site of aldose reductase with the combination of gigantol and syringic acid for prevention of diabetic cataract

Abstract: BackgroundGigantol and syringic acid (SA) have been shown to synergistically prevent formation of diabetic cataract (DC). However, the exact mechanism of this effect is unknown. Here, we investigate the effect of these compounds on the activity of aldose reductase (AR) and cataract formation.MethodsWe examined the synergistic anti-cataract efficacy of gigantol and SA in the high glucose- and streptozotocin -induced DC rat model; synergism was evaluated using Jin’s formula. We investigated possible mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…The number of people with diabetes worldwide has exploded in the past several years and is expected to sustain rapid growth. Long-term and uncontrollable high blood glucose generates various diabetic complications, including DR [34]. A global epidemiological analysis showed that 35% of people with diabetes have some form of DR [36], which is characterized by a progressive alteration in retinal microvasculature, leading to capillary closure [24].…”
Section: Discussionmentioning
confidence: 99%
“…The number of people with diabetes worldwide has exploded in the past several years and is expected to sustain rapid growth. Long-term and uncontrollable high blood glucose generates various diabetic complications, including DR [34]. A global epidemiological analysis showed that 35% of people with diabetes have some form of DR [36], which is characterized by a progressive alteration in retinal microvasculature, leading to capillary closure [24].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on its bioactive constituents demonstrated that gigantol ( Figure 2 ), an important bioactive constituent, has a synergistic effect with syringic acid ( Figure 2 ), and plays an important role in preventing diabetic cataracts by inhibiting aldose reductase activity through downregulation of its expression via reduced transcription, and by controlling sorbitol levels. The synergistic effect is thus mainly due to disruption of AR activity and the polyol pathway [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many plants exhibit potential pharmacological activities and antidiabetic effects, but thus far no standardization and toxicological experiments have been carried out using the active ingredient as a biomarker. For example, while C. religiosum is commonly employed to treat jaundice, syphilis, and gonorrhea, and is a source of two bioactive constituents, namely isorhamnetin and myricetin (Stefek [ 28 ]), and D. chrysotoxum is a rich source potential agents such as gigantol and syringic acid, having antihyperglycemic, antioxidant, immunomodulatory, and anti-tumor effects [ 36 ], no standardization study aimed at reliably getting high-quality extracts from these plants has been performed to date. Fruit pericarp L. Chinensis , usually wasted after eating the fruit, is a rich source of polyphenols and tannins, having potential ethnopharmacological anti-tussive, antipyretic, analgesic, and diuretic properties, could be utilized as a source of antidiabetic agents in different pharmaceutical industries [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that gigantol, which is a natural compound extracted from Dendrobium draconis , has a variety of bioactivities as well as antitumor effects in liver and lung cancers 25,26,29,36,37. To our knowledge, it has not been used in anti-CRC therapy by itself or as a sensitizer for existing anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%